The Influence of Leverage and Profitability on Tax Avoidance with Institutional Ownership as a Moderating Variable: Empirical Study on Food and Beverage Manufacturing Companies Listed on the Indonesia Stock Exchange in 2021-2024 (Jurnal Literasi Akuntansi, 2026)
Purpose: This study aims to examine whether the effect of leverage and profitability on tax avoidance with institutional ownership as a moderating variable. Data were analyzed using SPSS 27.Method: This study utilizes quantitative data from the official websites of food and beverage sector companies, specifically manufacturing firms listed on the Indonesia Stock Exchange (IDX) in the 2021-2024 period with purposive sampling technique resulting 177 in total annual financial reports analyzed. The analytical methods used include multiple linier regression and subgroup analysis.Finding: The results of this study indicate that leverage has a possitive influence toward tax avoidance, profitability has a possitive effect in tax avoidance, institutional ownership can moderate the possitive of leverage on tax avoidance, and institutional ownership cannot moderate the possitive effect of profitability on tax avoidance.Novelty: This research is novel because the researches added a new time period 2021-2024. This research can make a significant contribution to the literature on tax avoidance and corporate finance, and can help improve understanding of how institutional ownership affects the relationship between leverage and profitability on tax avoidance.
Keywords: Leverage; Profitability; Tax Avoidance; Institutional Ownership